Kreative Maschinen und Urheberrecht Die Machine Learning-Werkschöpfungskette vom Training über Modellschutz bis zu Computational Creativity - Käde, Lisa (Datenrecht und neue Technologien, 2021)
The interdisciplinary analysis examines machine learning (ML) frameworks used in AI development and gives practical answers to copyright issues arising in this matter. A special focus lies on database protection of ML models. Furthermore, the thesis offers an opinion on text and data mining restrictions in the AI context. Regarding the production of potentially copyrightable works by means of ML, the author discusses the issue of copyright attribution, suggests a solution, and proposes a flow chart to identify the author in various scenarios. In view of a potentially increasing autonomy of AI, an introduction to the interconnection of the concepts of intelligence, creativity and Computational Creativity is provided.